2020
DOI: 10.1080/09687637.2020.1822293
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol drinking among adolescents with native-Swedish and non-European immigrant background: the importance of parental attitudes and peer attitudes for acculturation

Abstract: In this study, we examine differences in alcohol drinking between first-and second-generation non-European immigrant and native-Swedish adolescents. We also examine whether parental and peer attitudes toward alcohol are associated with the acculturation of drinking habits among adolescents with an immigrant background. The study is cross-sectional and based on a school survey conducted in 2016-2019 in eight municipalities in southern Sweden. The sample consists of 3743 adolescents in year 9 of compulsory educa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
(98 reference statements)
0
6
0
Order By: Relevance
“…The data used are based on secondary data analysis from four cross-sectional surveys from the Öckerö project [51,52], an evaluation of an alcohol prevention program [53].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data used are based on secondary data analysis from four cross-sectional surveys from the Öckerö project [51,52], an evaluation of an alcohol prevention program [53].…”
Section: Methodsmentioning
confidence: 99%
“…The scale has an alpha value of .87. This scale has previously been used in the study of alcohol use [51]. Similar measures have been used in previous research [16].…”
Section: Dependent Variablementioning
confidence: 99%
“…The study is based on secondary data analysis from the Öckerö project [ 32 , 33 ], an evaluation of an alcohol prevention program [ 34 ]. The project included an annual, anonymously completed, cross-sectional online self-report survey, which was conducted at 17 secondary schools in eight small municipalities in the county of Skåne.…”
Section: Methodsmentioning
confidence: 99%
“…Approximately 10% of Danish young people do not drink alcohol, and among young Danish people with a Muslim background, around 70% are abstainers (Gundelach & Järvinen, 2006). Likewise, studies from other Nordic countries have found that young Muslim women have significantly lower rates of drug and alcohol use than ethnic majority young people (Johnson & Svensson 2020;Øia 2013;Bergengen & Larsen 2008;Skrowny 2005).…”
Section: Introductionmentioning
confidence: 98%